Induction of Manganese Superoxide Dismutase by Nuclear Translocation and Activation of SIRT1 Promotes Cell Survival in Chronic Heart Failure - Tanno, Masaya (American Society for Biochemistry and Molecular Biology, 2010)
Oxidative stress plays a pivotal role in chronic heart failure. SIRT1, an NAD(+)-dependent histone/protein deacetylase, promotes cell survival under oxidative stress when it is expressed in the nucleus. However, adult cardiomyocytes predominantly express SIRT1 in the cytoplasm, and its function has not been elucidated. The purpose of this study was to investigate the functional role of SIRT1 in the heart and the potential use of SIRT1 in therapy for heart failure. We investigated the subcellular localization of SIRT1 in cardiomyocytes and its impact on cell survival. SIRT1 accumulated in the nucleus of cardiomyocytes in the failing hearts of TO-2 hamsters, postmyocardial infarction rats, and a dilated cardiomyopathy patient but not in control healthy hearts. Nuclear but not cytoplasmic SIRT1-induced manganese superoxide dismutase (Mn-SOD), which was further enhanced by resveratrol, and increased the resistance of C2C12 myoblasts to oxidative stress. Resveratrol's enhancement of Mn-SOD levels depended on the level of nuclear SIRT1, and it suppressed the cell death induced by antimycin A or angiotensin II. The cell-protective effects of nuclear SIRT1 or resveratrol were canceled by the Mn-SOD small interfering RNA or SIRT1 small interfering RNA. The oral administration of resveratrol to TO-2 hamsters increased Mn-SOD levels in cardiomyocytes, suppressed fibrosis, preserved cardiac function, and significantly improved survival. Thus, Mn-SOD induced by resveratrol via nuclear SIRT1 reduced oxidative stress and participated in cardiomyocyte protection. SIRT1 activators such as resveratrol could be novel therapeutic tools for the treatment of chronic heart failure.